MENINGKATKAN HASIL BELAJAR IPA TENTANG PERUBAHAN KENAMPAKKAN PERMUKAAN BUMI DAN BENDA LANGIT MELALUI PETA PIKIRAN PADA ANAK KESULITAN BELAJAR KELAS IV SD 13 BALAI-BALAI KOTA PADANG PANJANG - Yosi - Purwasari (Jurnal Penelitian Pendidikan Khusus, 2013)
ABSTRACT This study begins with observation and interviews with researchers fourth grade teacher, the class IV there are 14 students who have difficulty in mastering the subject matter of Natural Sciences, was bored with the material of Natural Science is too much and have difficulty in working on the Natural Sciences . So the Natural Sciences learning outcomes of students after it does not fit with the Daily Deuteronomy KKM set by the school, whereas in other subjects such as Mathematics, English, SBK, Physical Education and Health KKM children have a value above the specified school. Therefore the action through the creation of mind maps. This study aims to improve the learning process concerning the Physical Sciences landscape surface of the Earth and sky objects, so as to improve the learning outcomes of the Natural Sciences learning difficulties in students in the fourth grade-District 13 Padang Panjang City. The approach used in this study is a qualitative approach. The research data in the form of information about the process obtained from observations, test results and a discussion of the learning process. The data source is the process of the administration of the Natural Sciences learning through mind map learning difficulties in students in the fourth grade-District 13 Padang Panjang City. Research subjects consisted of students' learning difficulties Elementary School fourth grade-District 13 Padang Panjang City, a total of 14 people, consisting of men and women 8 people 6 people. Procedure of the research conducted through four phases: 1) planning 2) implementation, 3) observation, 4) reflection. From the results obtained by the results of research conducted on average students in the first cycle an average of 58.57 and the second cycle, the average value of 75.71 students. The conclusion of this study is to map the mind can improve learning outcomes Physical Sciences landscape changes on the surface of the Earth and of celestial bodies on student learning difficulties.